CI-FLOW: Evaluating and Testing New Technologies for Accurate and Timely Identification of Inland and Coastal Floods in the Tar-Pamlico and Neuse River Basins of Coastal North Carolina - Van Cooten, Suzanne; Thigpen, Jack; Bacon, Robert (My University, 2009)
CI-FLOW is a new technology being utilized to identify flood hazards. CI-FLOW stands for the Coastal and Inland Flooding Observation and Warning project. CI-FLOW was implemented ten years ago by the directors of Sea Grant and NOAA, along with other North Carolina partners and state agencies. The National Weather Service has one forecast point in Louisburg, NC, on the Tar River. The addition of additional USGS gauges is important for effective identification of flood hazards. The accurate and timely identification of flood hazards is important given the growing and seasonally fluctuating population of Dare County. Approximately one-half of the housing in Dare County is seasonal, and emergency mangers must account for this. For instance, it is estimated that in 2030, if a category three hurricane hit during a time of peak tourism, emergency managers would need to clear 30,000 vehicles in 31 hours. Given the importance flood identification, an integrated approach is needed for accurate and timely identification. The utilization of storm surge models and observations of weather and river levels, is key in flood identification. Three-dimensional images linked with real-time data can help assess the dangers of a flood and aid in emergency management decisions. CI-FLOW is being used to time crests and discharges along with a coupled model which links water and storm surge discharge. In conclusion, the CI-FLOW project is a multi-agency evaluation of new technologies to better identify floods in the Tar-Pamlico and Neuse river basins.
Keywords: NCEM; Hurricanes; Emergency management; Emergency disaster